Translating the complexities of flood risk science using KEEPER – a knowledge exchange exploratory tool for professionals in emergency response. Issue 3 (9th April 2013) - Alexander, M.; Viavattene, C.; Faulkner, H.; Priest, S.
Abstract Within flood risk management (FRM) decision making, there is a growing interest in participatory approaches to engage and integrate stakeholder expertise. Decision support tools are becoming common features in the FRM 'toolkit', yet there is a limited application of participatory methodologies in the construction of such tools. This paper reports on completed FRMRC research (Flood Risk Management Research Consortium, UK http://www.floodrisk.org.uk/) and the construction of a geographic information system‐based flood risk assessment tool, KEEPER – a Knowledge Exchange Exploratory tool for Professionals in Emergency Response. An iterative methodology was used to engage emergency professionals throughout the research process, allowing a mixing of scientific and professional expertise in the co‐production of KEEPER. KEEPER was both instrumental in facilitating participation and knowledge exchange, and informing recommendations for future tools in practice. This paper argues that participation is both essential for supporting pragmatic flood research and as a means of enhancing communication across traditionally divided communities.